ӘДЕБИЙ-ИЛИМИЙ ҲҮЖДАН ҲӘМ ҲУҚЫҚЫЙ ТӘРБИЯ МӘСЕЛЕЛЕРИ - Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2016)
The article deals with the role of legal education in the development of scientific and literary conscicusness in the students of schools, secondary special professional and higher educational establishments in the system of continuous education.
Keywords: scentific consciousness; system of continuous education; legal education and upbringing; plagiarism; to possess an idea of the other person; literary plagiarism; the author‘s right